Post-Trip Recollections of Austrian Volunteer Tourists – A Narrative Enquiry - Hauptmann, Carina (2014)
Tourism as a constantly growing industry is facing various challenges in terms of sustainability and global development. As an alternative to mass tourism, distinct – arguably more ‘ethical’ forms of tourism – have emerged over the last few decades. Volunteer tourism can be regarded as part of this evolution as well as a form of travelling aimed at combining both altruistic intentions of volunteering and self-interested pursuits comparable to ‘normal holidays’.